Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae) ability to breed and damage potential on cassava dried chips (2001)
Stored dried cassava chips are known to become heavily damaged by Prostephanus truncatus (Hum). A laboratory study was undertaken to determine the extent of losses that this insect pest could cause on TME 30572, the mean weight loss (±SD) rose to 36.93 ± 24.43% over the period of 112 days compared with 63.2 ± 3.37% for TME 1, under the same period and experimental condition, At each time interval of 28 days during which the cassava dried chips were examined, the weight loss in both varieties was on the increase, except, the 112 days where their was a drop in the weight loss in TME 30275 variety which was statistically significantly (t=0.033, P<0.05). Percentage mortality rate rose from 0% to 10.6% in TME 30572 larval, while zero mortality was recorded for TMEI larval. On the other hand, percentage mortality was on the increase in emergent adults for both cassava varieties. The highest percentage mortality in TME1 emergent adult was inflicted in TME1. However, storing TME 30572 rather than TME1 will not solve the problem of infestation and damage by P. truncatus because considerable damage is been inflicted on TME 30572. The experiment was conducted under ambient temperature of 30.3 ± 3.7°C and relative humidity of 84.7 ± 2.0% in the laboratory.